The Parameterization of All Stabilizing Multi-Period Repetitive Controllers for Multiple-Input/Multiple-Output Plants With the Specified Input-Output Frequency Characteristic - Yamada, Kou; Nakazawa, Nobuaki; Sakanushi, Tatsuya; Yamamoto, Shun; Nguyen, Nhan Luong Thanh (ECTI Transactions on Electrical Engineering, Electronics, and Communications, 2010)
In this paper, we examine the parameterization of all stabilizing multi-period repetitive controllers for multiple-input/multiple-output plants with the specified input-output frequency characteristic. The parameterization of all stabilizing multi-period repetitive controllers, those are used to improve the disturbance attenuation characteristics of the repetitive controller, for non-minimum phase systems was solved by Yamada et al. However, when we design a stabilizing multi-period repetitive controller using the parameterization by Yamada et al., the input-output frequency characteristic of the control system cannot be settled so easily. From the practical point of view, the input-output frequency characteristic of the control systems is required to be easily settled. This problem is solved by obtaining the parameterization of all stabilizing multi-period repetitive controllers with the speci¯ed input-output frequency characteristic. However, no paper has proposed the parameterization of all stabilizing multi-period repetitive controllers for multiple-input/multiple-output plants with the speci¯ed input-output frequency characteristic. In this paper, we propose the parameterization of all stabilizing multi-period repetitive controllers for multiple-input/multiple-output plants with the specified input-output frequency characteristic.